Gender-based roles, psychosocial variation, and power relations during delivery and postnatal care: a qualitative case study in rural Ethiopia - Shibeshi, Ketema; Lemu, Yohannes; Gebretsadik, Lakew; Gebretsadik, Abebe; Morankar, Sudhakar (Frontiers in Global Women's Health, 2023)
The World Health Organization (WHO) strongly encouraged men to support women in maternal health care services. However, especially in developing countries, maternal health care has traditionally been viewed as a women's issue, with men making little or no contribution, even though sexuality and children are shared products. The study aims to understand how genderbased roles, psychosocial variation, and power relations are related to child delivery and postnatal care services. The study took place in three rural districts of Ethiopia, Oromia regional state, Jimma Zone. An in-depth interview and focus group discussion were held with carefully chosen health professionals, health extension workers, community health development armies, and religious leaders. The data was collected, translated, and transcribed by experienced men and women qualitative researchers. For data analysis, Atlas Ti version 9 was used. The data was coded and categorized concerning delivery and postnatal care service utilization. Independent and shared gender-based roles were identified as a means to improve maternal health care service delivery. The result obtained three categories; Gender-based roles, psychosocial variation, and power relations. Men can persuade pregnant women to use delivery services and postnatal care.The place of delivery is determined by the levels of gender power relations at the household level, but women are usually the last decision-makers. The community's belief that giving birth in a health facility makes women look clean and neat, as opposed to home delivery, increases their intention to use maternal health care services. The study contributes that the role of a man as a husband is crucial in mobilizing others to carry pregnant women to health facilities, contributing to early intervention during labor. Women's decision-making capacity has improved over time, with men accepting their right to make decisions about their health and fetuses. Home delivery and men not being escorted during delivery are signs of backwardness while giving birth in health institutes is seen as a sign of modernization and women's rights. The keywords are